DEVELOPMENT OF PERFORMANCE EVALUATION AND OPTIMIZATION METHOD OF WEBSITE USING METRICS CORELATION APPROACH - 1. Diksikumari Suthar, 2. Dr. Seema Mahajan , 3. Dr. Nimisha Patel (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
We have proposed a method for selecting most affecting metrics with page loading speed of the site by corelation technique. We have formed a list of criteria that affect the site loading speed. We have discovered the difficulties and shortcomings of certain criteria, which should be considered as analytical and theoretical data for an expert review of the complexity of criteria implementation. The weighting factors of the criteria influence on the optimization degree of the website loading speed are determined. A pairwise comparison matrix of criteria is based on determining how much one of the criteria is influencing the optimization degree of the site loading speed more significant than the other. The calculation of the elements of the weighting matrix of the criteria is implemented. We have formed an order of the criteria list implementation to increase the site loading speed. The implementation of the developed methodology for optimizing the site loading speed was implemented on sample version of Drupal 9.5 content management system. We have reviewed several alternatives for the implementation of image compression. The site loading speed has been tested before and after the implementation of the developed method. It has been determined that, on average, site loading speed indicators improved by 42 %. We have developed innovative approaches to select most relevant criteria in improving page load and rendering of web resources on all devices, including techniques such as resource minification, compression, lazy loading, and prioritized loading based on user interactions. This development will support webmaster and decision-makers in the form of statistical data and comparison table to understand which method to be best suitable for their site.